Management of natural wealth – resources curse and socio-economic development - Ristić, Vladimir; Mirković Isaeva, Olga; Vasić, Bojana (Industrija, 2018)
The phenomenon of the resource curse is based on the assumption that countries with large natural resources are unable to achieve adequate economic development, and cannot provide benefits to their citizens. High impact on this issue lays in inadequate management of human resources and corruption. The main objective of this paper is to examine the basic assumptions of the theory of resource curse, to determine the factors that have the greatest impact on its (non)existence, to determine the causal dependence between natural wealth and the political environment, as well as with the quality of life of citizens. The research was carried out by analysing five variables that define resources curse and Human Development Index. For data processing, Fisher’s F test is applied. The survey was done on a sample of 22 countries. The results show: a) the characteristics of the political regime do not have a clearly defined impact on existence of resource curse, b) resources rent and export of energy products do not have a significant impact on the quality of life of citizens (expressed through the Human Development Index) and c) a significant degree of deviation from the expected is determined in countries rich in ores and metals.